Substitution of Notions of “Russia” and “U.S.S.R” in “The New York Times” Newspaper (1946-1991) - E. A. Kotelenets; M. S. Zatulovskaya (Научный диалог, 2019)
The frequency of mentioning the words Russia , Soviet Union , Soviet Russia and U.S.S.R in the American press is in order considered to analyze the stereotypical views of Americans about our country during the cold war. As a source the articles published in the daily newspaper “The New York Times” in the period from 1946 to 1991 are used. The authors analyzed more than 40 000 newspaper articles. The hypothesis about the relation between the frequency of use of various country nominations and the formation of stereotypes about it is offered. The research methodology is based on the statistical analysis of the use of the words Russia , Soviet Union , Soviet Russia and U.S.S.R in “The New York Times” publications. It is revealed that during the cold war the frequency of using the word Russia in this newspaper exceeds the frequency of using the word U.S.S.R 10 times, that, according to the authors, leads to the conclusion about the substitution of notions, which is expressed in the identification of pre-revolutionary Russia and the Soviet Union. It is shown that in the future there was a reverse process: during the period of tension of political relations, the image of Russia began to be replaced in American newspaper publications by the image of the USSR, which in the minds of Americans is closely connected with the cold war.